The Role of Erythritol/Glycine Air Polishing Powder In Non-Surgical Periodontal - Mohammed Khalid Ayoob / Hayder Raad Abdulbaqi ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2024)
Objective: This narrative review assesses the literature on the effectiveness of erythritol/glycine powder air polishing (EPAP/GPAP) in non-surgical periodontal treatment (NSPT) in terms of improving the clinical and microbiological parameters of periodontium status after air-polishing debridement. Methods: A detailed search of the literature was conducted in the following electronic databases: Google Scholar, PubMed, and Scopus. The inclusion criteria encompassed systematic reviews with meta-analyses that were published throughout the timeframe of 2014 to 2022, and human, peer-reviewed clinical studies examining the efficacy of usage of air-polishing devices in the treatment of periodontitis that were published between 2008 to 2022. Results: The search yielded 4 systematic reviews and 6 original research papers, encompassing a total of 8 clinical investigations. Conclusion: The selected literature lacked data that included a long-term evaluation of more than 12 months on the effect of air polishing powder in non-surgical periodontal treatment. Regardless of that, powder air polishing showed a comparable outcome compared with scaling root planning (SRP) with the superiority of powder air polishing in terms of antimicrobial effectiveness and exhibits better patient experience